2014
DOI: 10.1021/je500571k
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Equilibrium of Primary and Secondary Aqueous Two-Phase Systems Composed of Sucrose + Triton X-114 + Water at Different Temperatures

Abstract: Liquid−liquid equilibrium (LLE) data for aqueous twophase systems (ATPSs) composed of sucrose, Triton X-114, and water were determined at 288 K, 293 K, and 298 K. At 293 K and 298 K, the top and bottom phases of the ATPS were enriched with sucrose and Triton X-114, respectively. However, phase inversion was observed in the ATPS formed at a lower temperature (288 K). When the temperature increased, the area of the biphasic region became larger, whereas the slopes and the lengths of the tie lines decreased. Bino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The binodal data of polymer–salt ATPSs was correlated by the third-order polynomial equation (eq ), and the equation analogue effect was good. Equation was widely used to fit the binodal curves of many ATPSs. ,,, In this work, the experimental binodal data of three ATPSs were regressed and analyzed by computer and the fitting parameters a , b , c , and d of three euqations were given in Tables – , where the square of correlation coefficients ( R 2 ) and the corresponding standard deviations (sd) were also shown. It was found that eq has a higher goodness-of-fit than the other two equations by comparison of the correlation coefficients and standard deviations given in three tables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binodal data of polymer–salt ATPSs was correlated by the third-order polynomial equation (eq ), and the equation analogue effect was good. Equation was widely used to fit the binodal curves of many ATPSs. ,,, In this work, the experimental binodal data of three ATPSs were regressed and analyzed by computer and the fitting parameters a , b , c , and d of three euqations were given in Tables – , where the square of correlation coefficients ( R 2 ) and the corresponding standard deviations (sd) were also shown. It was found that eq has a higher goodness-of-fit than the other two equations by comparison of the correlation coefficients and standard deviations given in three tables.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding tie-lines were shown in Figures – . As the widespread empirical correlation equations, the Othmer–Tobias and Bancroft equations (eqs and ) were used to correlate the tie-line compositions of many ATPSs. ,,, , In investigated systems, the tie-lines data was fitted by using these two equations where w stands for the mass fraction of materials in ATPS, the subscripts “1”, “2”, and “3” respectively represent three substances of systems (POELE20, salt, and water), the superscripts “t” and “b” represent two phases of ATPS (the top phase and bottom phase), and k 1 , k 2 , n , and r were the fitting parameters whose values were shown in Table . The square of correlation coefficient values ( R 2 ) and standard deviations (sd) were shown in Table , and it was found that these two equations were qualified for the studied systems.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of DIMCARB in phase solutions was measured spectrophotometrically using a UV–vis spectrophotometer at 350 nm. Then, the samples were subjected to vacuum drying using a freeze-dryer (CoolSafe series, ScanVac) at 181 K for 24 h . Both DIMCARB and water were vaporized after the drying, leaving the PPG as the residue.…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of IL in both phases were determined using an UV–vis spectrophotometer (Cary 100 UV–vis, Agilent Technologies) at 277 nm. To quantify the water content of the top and bottom phases, the samples were subjected to vacuum-drying at −92 °C for 24 h using a freeze-dryer (CoolSafe series, ScanVac) . The weight loss in the sample was equivalent to the mass of the water in the system.…”
Section: Methodsmentioning
confidence: 99%